2019
DOI: 10.1097/tp.0000000000002249
|View full text |Cite
|
Sign up to set email alerts
|

Split Liver Transplantation and Pediatric Waitlist Mortality in the United States: Potential for Improvement

Abstract: This comparison, while not conclusive, suggests that we might be missing opportunities to reduce pediatric waitlist mortality without decreasing access for adults-using split liver transplant. Barriers are significant, but further work on strategies to increase split liver transplant is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 16 publications
4
89
0
2
Order By: Relevance
“…Although the risks associated with SLT did decrease significantly with improved techniques and experience, the authors found that the number of SLT patients remained at ~60 per year. This is consistent with the finding by Perito et al of SLT being underused with only 3.8% of potentially splittable livers used for SLT . In addition, Sasaki et al caution against the conclusions made by other authors that SLT can achieve comparable graft/patient outcomes compared with WLT, noting that SLT is still more hazardous in the early period after transplantation.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Although the risks associated with SLT did decrease significantly with improved techniques and experience, the authors found that the number of SLT patients remained at ~60 per year. This is consistent with the finding by Perito et al of SLT being underused with only 3.8% of potentially splittable livers used for SLT . In addition, Sasaki et al caution against the conclusions made by other authors that SLT can achieve comparable graft/patient outcomes compared with WLT, noting that SLT is still more hazardous in the early period after transplantation.…”
supporting
confidence: 82%
“…Despite being introduced decades ago and frequently used in the pediatric population, SLT remains underused in adult candidates with stagnant case volumes . From 2004 to 2014, utilization of split livers in adults varied merely by 0.2% (between 1.0% and 1.2%) .…”
mentioning
confidence: 99%
“…These findings should be considered in the context of work by Hsu et al that showed nearly half of the children who died on the waiting list never received a single offer of a liver . Furthermore, recent research by Perito et al showed that approximately half of the most splitable livers, by strict criteria, were not used for SLT …”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] However, access to timely LT is challenging for children due to the scarcity of size-matched pediatric deceased donors. [5][6][7][8][9] Despite these approaches, obtaining size-matched partial liver grafts that are small enough for many pediatric recipients remains a problem. [5][6][7][8][9] Despite these approaches, obtaining size-matched partial liver grafts that are small enough for many pediatric recipients remains a problem.…”
Section: Liver Transplantation (Lt) Is An Established Life-saving Trementioning
confidence: 99%